Expression of recombinant porcine reproductive and respiratory syndrome virus nucleocapsid protein with antigenicity and immunogenicity study: https://doi.org/10.12982/VIS.2022.029 - Suwankitwat, Nutthakarn; Starrat, Wachareeporn; Sagumpung, Preeyanuch; Ratthanophart, Jadsada R (Veterinary Integrative Sciences, 2022)
Porcine respiratory and reproductive syndrome virus (PRRSV) causes significant economic losses in the swine industry worldwide. Nucleocapsid protein (NP) encoded by ORF7 is the most abundant and high immunogenicity. However, there were only few studies on recombinant NP expression with antigenicity and immunogenicity from PRRSV in Thailand. The aim of this study was to express rNP from PRRSV found in Thailand and evaluate its antigenicity and immunogenicity. ORF7 gene was amplified by RT-PCR. The PCR products were cloned into pGEM®-T Easy vector, and subcloned into pET-24a (+) expression vector and transformed into E. coli. The rNP properties were proved by SDS-PAGE and Western blot. The antigenicity of rNP was evaluated by indirect ELISA comparing to a commercial test kit. The immunogenicity of rNP was proved by rabbit immunization. Then, the antiserum was tested with tissues from PRRSV-infected swine by immunohistochemistry (IHC). In addition, amino acid sequence of the rNP was analyzed and compared to PRRSV reference strains. The PCR products of a whole ORF7 gene were 388 bp. The rNP size was 18 kDa. The indirect ELISA assay showed high antigenicity of the rNP with 100% sensitivity and 93.33% specificity at 0.25 O.D. cutoff value. The rNP could induce specific antibody production in the rabbit, which reacted specifically to PRRSV in tissues by IHC. The amino acid sequence of the rNP had similarities to US, HP-PRRSV and EU PRRSV at 95.93-99.19%, 96.75%, and 57.03-61.47%, respectively. Our rNP can be used for PRRSV diagnosis and test kit development.